Case report: Ultrasound-guided multi-site electroacupuncture stimulation for a patient with spinal cord injury - Song, Xi-Zi; Chu, Xiao-Lei; Liu, Tao; Cao, Yu-Tong; Li, Rui-Xin; Gao, Ming-Wei; Li, Qing-Wen; Gu, Xiao-Song; Ming, Dong (Frontiers in Neurology, 2022)
Introduction:Spinal cord injury cause s permanent neurological deficits, which have devastating physical, social and vocational consequences for patients and their families. Acupuncture, which originates from traditional Chinese medicine, has been used to reduce neuropathic pain and improve nerve conduction velocity. It also prevents joint contracture and muscle atrophy in patients with peripheral nerve injury. Electrical stimulation therapy for injured nerves in animal and human models has resulted in satisfactory recovery. Case Description: A 48-year-old female patient was hit by a heavy object that injured her lower back. The patient had a T12- L1 vertebral flexion and stretch fracture with traumatic spinal stenosis. The patient was transferred to the rehabilitation department after posterior T12-L2-segment pedicle screw system distraction and reduction, internal fixation, decompression and bone graft fusion. Ultrasound-guided electroacupuncture was used to stimulate the sacral nerve, spinal nerve and the head of the patient, accompanied by spinal joint loosening training, respiratory training, lumbar comprehensive sports training, paraplegic limbs comprehensive training and other manipulation treatment. Outcomes: After intervention, patients showed significant improvements in sensory and motor scores resulting to functional recovery according to ASIA and FIM. Patients gradually show functional remission. Discussion: This case report shows the outcome of one patient. The sacral nerve, spinal cord and head were electrically stimulated by ultrasound-guided electroacupuncture for intervention, and various functions of the patient were alleviated to a certain extent. Future clinical trials should examine the efficacy of ultrasound-guided electroacupuncture stimulation in treating neurologic symptoms.